PENDAPATAN, HARGA POKOK PRODUKSI (HPP) DAN HUBUNGANNYA DENGAN FAKTOR PRODUKSI UBIKAYU DI PROVINSI LAMPUNG - Seta, Amanda Putra; Zakaria, Wan Abbas; Endaryanto, Teguh; Indah, Lidya Sari Mas; Hermawan, Dedy (Lampung University, 2024)
The selling price of cassava is still a major problem that always arises from year to year. Low selling prices below cassava production costs cause losses for farmers. This research aims to analyze the cost of production (HPP) of cassava and its relationship with cassava production factors in Lampung province. This research was conducted in Lampung Province using a survey method with a total of 210 cassava farmers consisting of cassava farmers in East Lampung, Central Lampung and West Tulang Bawang Regencies. These three areas were chosen because they are cassava production centers in Lampung Province. The analysis used for the cost of production uses the full costing and variable costing methods, apart from that the analysis of the relationship to production factors is analyzed using multiple linear regression using the ordinary least squares (OLS) method. The amount of profit or loss borne by farmers is analyzed using R/C or the comparison of total revenue obtained with total costs incurred. Based on the results of the study, it was found that the variable costing HPP for cassava was IDR 453/kg and the full costing HPP was IDR 698/kg. Income from cash costs of cassava farming per hectare is IDR 7,410,379.11/ha and income from total costs is IDR 1,711,995.55/ha with an R/C value for cash costs of 2.06 and R/C for total costs of 1.03, which means that cassava farming in Lampung Province is profitable to cultivate. Apart from that, production factors that are significantly related to the cost of production are land area and seed prices. Both have a positive influence on the Ubikayu HPP in Lampung Province. keywords: Full Costing,Production Factors, Profit